Relationship Between Fundamental Motor Skill Competence, Perceived Physical Competence and Free-Play Physical Activity in Children. Issue 1 (2nd January 2020) - Tsuda, Emi; Goodway, Jacqueline D.; Famelia, Ruri; Brian, Ali
ABSTRACT: Purpose : This study examined the extent to which fundamental motor skill competence (FMSC; locomotor and object control skill competence) and perceived physical competence (PPC) predicted physical activity levels and sedentary behaviors during free-play time at preschool. Method : A total of 72 children (girls n = 33, boys n = 39; M age = 4.38, SD = .85 years) were recruited from two preschools. Fundamental motor skill competence was measured using the Test of Gross Motor Development − 2nd edition, and PPC was assessed using the physical competence subscale of the Pictorial Scale of Perceived Competence and Social Acceptance. Physical activity was measured using accelerometers. Results : Children engaged in light physical activity 19.66%, and moderate to vigorous physical activity (MVPA) 36.41%, and sedentary behaviors 43.94% of their free-play time. Since no correlation was observed in light physical activity with any variables, a hierarchical multiple linear regression was run for MVPA and sedentary behaviors. The results illustrated 38.9% of the variance in MVPA during free-play time was predicted by FMSC and PPC, after controlling for age and sex, with locomotor skill competence as a significant predictor ( t = 2.98, p < .05). For sedentary behaviors, the 32.9% of the variance during free-play time was predicted by FMSC and PPC, after controlling age and sex, with locomotor skill competence as a significant predictor ( t = 2.72, p < .05). Conclusion : The findings highlight the importance of developing FMSC and positive PPC during early childhood to enhance physical activity engagement during free-play.